Evaluasi kesesuaian peresepan obat terhadap formularium nasional di Rumah Sakit Umum Daerah Sumbawa tahun 2021 - Titania Nabilah; Ni Made Amelia Ratnata Dewi; Siti Rahmatul Aini (Sasambo Journal of Pharmacy, 2023)
Hospitals should follow the National Formulary when prescribing medications. In accordance with the National Formulary, the percentage of drug prescriptions in a hospital must be at least 80%, according to the health service quality indicator standard number 30 of 2022 about hospital prescriptions. One of West Nusa Tenggara Province's class C hospitals, the Sumbawa Regional General Hospital treats patients with National Health Insurance (NHI), whose population is steadily growing. The purpose of this study is to assess the Sumbawa Regional General Hospital's suitability to prescribe medications in 2021 in accordance with the National Formulary. Retrospective data gathering is used in the observational research design. Based on inclusion and exclusion criteria, the research sample consisted of all prescription sheets for both inpatients and outpatients at the Sumbawa Hospital from January to December 2021. Prescription forms, drug content, dosage strengths, and dosing forms are all indicators of eligibility for prescribing. By comparing the number of prescriptions for drugs written according to the National Formulary with the total number of prescriptions, the suitability percentage was computed. The National Formulary states that 87.65% of medication items are suitable for prescription. According to the National Formulary, 87.65% of medicine items were suitable, and 66.2% of prescription sheets were as well. The Sumbawa Hospital's prescriptions are not 100% in accordance with the National Formulary, yet based on drug items have exceeded the standard indicators of drug prescriptions on hospital (more than 80%).